Impact of Effective Leadership Behavior on TQM by Continuous Improvement - Abd Ali, Afnan; Abdlameer Ahmed, Ala (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this work is to establish a frame of reference for the study of the relationship between two concepts, effective leadership as independent and continuous improvement, traditionally treated as dependent, as well as the effect of the relationship on total quality management. After a brief review of the literature in each of the fields of study, we turn to relate these concepts, raising a series of research questions with which we intend to lay new foundations for future prescriptions on management aimed at improving total quality management by adopting continuous improvement by the leadership. The main instrument of the study is a survey and its analysis by using the structural modeling method. The study concluded that adopting leadership for continuous improvement contributes significantly to improving the total quality management of organizations.